1991
DOI: 10.1136/hrt.65.5.249
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine activity in untreated heart failure.

Abstract: Neuroendocrine activity was studied in 60 consecutive untreated patients with dyspnoea and a clinical suspicion of heart failure. On the basis of the socalled Boston clinical criteria the diagnosis of heart failure was regarded as unlikely in 26 patients, possible in 15 patients, and definite in 19 patients. These groups were studied before any drug treatment was started and were compared with a control group of 69 healthy individuals. Plasma atrial natriuretic peptide concentration was clearly raised in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 30 publications
5
19
1
2
Order By: Relevance
“…Our observations confirm and extend the findings of others who have shown that angiotensin activity is increased only in the more advanced phases of heart disease. 35 The dependence of the increase in renal thromboxane formation on angiotensin activation is underlined by its positive correlation with PRA, as observed in our study.…”
Section: American Heart Journalsupporting
confidence: 71%
“…Our observations confirm and extend the findings of others who have shown that angiotensin activity is increased only in the more advanced phases of heart disease. 35 The dependence of the increase in renal thromboxane formation on angiotensin activation is underlined by its positive correlation with PRA, as observed in our study.…”
Section: American Heart Journalsupporting
confidence: 71%
“…Moreover, among patients with LV dysfunction or heart failure, there is marked activation of the renin-angiotensin-aldosterone system. 11 Thus, it is unclear whether the findings documented in LV dysfunction or heart failure can be applied to patients with preserved systolic function and no sign of heart failure. The HOPE trial expanded the observations from these previous trials to high-risk persons with known preserved LV ejection fraction and without known heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Numerosi parametri bioumorali (norepinefrina, renina, endotelina-1) sono stati proposti come indici prognostici per lo scompenso cardiaco [45][46][47][48], tuttavia la loro validità è stata marcatamente influenzata da difficoltà di carattere tecnico come la conservazione dei campioni di sangue o la sovrapposizione tra valori normali e patologici. Queste problematiche risultano entrambe superate dal dosaggio ematico del BNP [49,40], che assomma anche il vantaggio di test bed-side rapido, prontamente disponibile e quindi particolarmente utile negli snodi decisionali.…”
Section: Il Bnp Come Guida Alla Terapia Ed Indice Prognostico a Mediounclassified